PERBANDINGAN PEMBELAJARAN ADVANCE ORGANIZER DENGAN KONVENSIONAL DALAM KETERAMPILAN BERPIKIR KRITIS DAN PEMAHAMAN KONSEP IPS DI KELAS VIII E DAN VIII F SMP NEGERI 1 MA’RANG KABUPATEN PANGKAJENE DAN KEPULAUAN - .,, Haerana; Yahya, Muh.; Yunus, Muh. (STKIP Pembangunan Indonesia Makassar, 2017)
This research is a type of research True Experimental Design (Real Experiment). This research was conducted in SMP One Ma’rang. In this study Population is the entire class VIII SMP One Ma’rang registered in 2016/2017 which amounted to 124 people. In this study the sample used are 42 people, consisting of 21 from class VIII E as the experimental class and 21 from class VIII F as the control class. In this research information about learning of Advance organizer and conventional learning by usingquestion instrument, while data of critical thinking skill and concept comprehension of student can be seen at result value of posttest. The gathering is done by using question instrument, observation and documentation. The results showed 1) There is a significant difference between the critical thinking skills of students who were taught with advanced organizational learning andwho were taught with conventional learning In class VIII E and VIII F SMP One Ma’rang,PangkajeneDistrik and Islands 2) There is a significant difference between Understanding of IPS concept of students who are taught by Advance Organizer learning in class VIII E and VIIIF SMP One Ma’rangPangkajeneDistrik and Islands. In line with the findings of the research results, one of the efforts that can be done in improving the thinking skills and understanding of the concept of IPS in Class VIII E and VIII SMP One Ma’rangPangkajeneDistrik and Islands. is advised to apply the Advance Organizer learning on certain material. Keywords: Advance Organizer Learning, Conventional Learning ,Critikal Thinking Skills, Understanding Concepts